PENGARUH GREEN ACCOUNTING, GOOD CORPORATE GOVERNANCE DAN FINANCIAL LEVERAGE TERHADAP FINANCIAL PERFORMANCE - Anjarningsih, Dwi; Lintang Kurniawati (ITB AAS Indonesia Surakarta, 2025)
Financial Performance is the main key for a company in running its business to attract investors. Oil and gas companies rank lowest in the investment attractiveness category. This study aims to test the effect of green accounting, good corporate governance proxied by the independent board of commissioners and audit committee and financial leverage proxied by the debt to equity ratio, debt to asset ratio and long-term debt to equity ratio on financial performance in oil and gas companies listed on the IDX 2020-2023. This study uses a quantitative method with secondary data processed using SPSS. With the purposive sampling method, 12 companies and 48 research sample data were produced that met the sample criteria. The test results show that green accounting, independent board of commissioners, audit committee, debt to equity ratio, debt to asset ratio and long-term debt to equity ratio have a joint effect on financial performance. Partially green accounting and long-term debt to equity have an effect on financial performance, but the independent board of commissioners, audit committee, debt to asset ratio and debt to equity ratio do not have an effect on financial performance.